2019
DOI: 10.3390/rs11131546
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Climatic Attributions of Autumn Land Surface Phenology Spatial Patterns in the Temperate Deciduous Broadleaf Forest of China

Abstract: Autumn vegetation phenology plays a critical role in identifying the end of the growing season and its response to climate change. Using the six vegetation indices retrieved from moderate resolution imaging spectroradiometer data, we extracted an end date of the growing season (EOS) in the temperate deciduous broadleaf forest (TDBF) area of China. Then, we validated EOS with the ground-observed leaf fall date (LF) of dominant tree species at 27 sites and selected the best vegetation index. Moreover, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…On August 29th and September 19th, we measured the reflectance spectra at 14:00 to 15:00 ( Table 1 ). Regarding the PSRI variation, horizontally sensing of a plant at the canopy level was only able to proportionally capture the carotenoid and mesophyll changes in the cell structure and leaves [ 82 , 88 ], and these proportions remarkably varied from plant to plant. Noticeably, no structural VI was found to be useful for spectral classification because of the similarity in canopy structure and color (i.e., greenness) between healthy and diseased plants in such asymptomatic periods.…”
Section: Discussionmentioning
confidence: 99%
“…On August 29th and September 19th, we measured the reflectance spectra at 14:00 to 15:00 ( Table 1 ). Regarding the PSRI variation, horizontally sensing of a plant at the canopy level was only able to proportionally capture the carotenoid and mesophyll changes in the cell structure and leaves [ 82 , 88 ], and these proportions remarkably varied from plant to plant. Noticeably, no structural VI was found to be useful for spectral classification because of the similarity in canopy structure and color (i.e., greenness) between healthy and diseased plants in such asymptomatic periods.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since the temperature is one of the important climatic factors affecting vegetation phenology (Cong et al, 2013;Liang and Zhang, 2016;Lang et al, 2019;Han et al, 2020), the seasonal curve of temperature in the high-, middle-, and low-latitude regions in different land cover types is shown in Figures 4-6. We can find that the fluctuations of temperature were similar in the same latitude region in different land cover types, but the fluctuations of vegetation curves (GPPs, SIF, and VIs) were different, which indicated that the phenological characteristics of different vegetation have different sensitivities to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…У дослідженні B. Ланг зі співроб. (Lang et al, 2019) виявили, що індекс старіння рослин найкраще являв просторовий розподіл змін рослинного покриву, що відбуваються восени наприкінці вегетації у листопадних широколистяних лісах помірного поясу в Китаї. Вчені припускають, що це може бути пов'язано з тим, що PSRI здатен фіксувати не тільки зміну структури клітин мезофілу, але й зміну відносної частки каротиноїдів та хлорофілу в листі, демонструючи більшу чутливість до старіння листя, ніж інші ВІ.…”
Section: рис 8 відношення між початковими і кінцевими значеннями ві рослинного покриву ярої пшениці сортуunclassified